A Study of the Effect of Volleyball Specific Training on the Explosive Force of the Legs of Players - Naresh Patel; Dr. R. D. Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was to A study of the effect of volleyball specific training on the explosive force of the legs of players. In this research study, 20 students in the volleyball specific training group of students studying at Ahmedabad Primary School and 20 students in the controlled group, a total of 40 students were selected as subject subjects. The differences between the mediators were measured at 0.05 by the Least Significant Difference Post Hock test by applying the One Way Analysis of Covariance test to find out the effects on the group. The conclusion was as follows. The 12-week volleyball specific training program saw a significant improvement in the explosive strength of the subjects.